2018
DOI: 10.1016/j.jjcc.2017.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of optimal cut-off value in inter-arm systolic blood pressure difference for prediction of cardiovascular events

Abstract: IAD is significantly associated with future cardiovascular events in patients with arteriosclerosis risk factors. The optimal cut-off value of IAD is 5mmHg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…desirable [31]. Finally, in the present study, antiplatelet therapy was mainly based on the use of aspirin and clopidogrel administration.…”
Section: Discussionmentioning
confidence: 87%
“…desirable [31]. Finally, in the present study, antiplatelet therapy was mainly based on the use of aspirin and clopidogrel administration.…”
Section: Discussionmentioning
confidence: 87%
“…This view is supported by some published work (Olmedillas et al, 2010) and it has been suggested that larger circumference arms may be associated with higher measured SBP (Loenneke et al, 2016). Furthermore, because of the widely reported potential significance of inter-arm SBP differences as a predictor of cardiovascular morbidity (Cao et al, 2015;Tokitsu et al, 2015;Zhou et al, 2016;Kranenburg et al, 2017;Hirono et al, 2018) it was believed that the issue concerning the role that handedness might play in such inter-arm pressure differences was of significance and should be specifically addressed. A third motivating factor was that most prior assessments of inter-arm pressure differences focused on either older persons or those with already present cardiovascular symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…This meant that there was little data on young and apparently healthy adults. Furthermore, because of the widely reported potential significance of inter-arm SBP differences as a predictor of cardiovascular morbidity (Cao et al, 2015;Tokitsu et al, 2015;Zhou et al, 2016;Kranenburg et al, 2017;Hirono et al, 2018) it was believed that the issue concerning the role that handedness might play in such inter-arm pressure differences was of significance and should be specifically addressed. This led to the working hypothesis that the magnitude of cuff pressures needed to compress the underlying brachial artery in determining SBP would be greater in the dominant arm thereby rendering the dominant arm to have a greater SBP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean blood pressure differences between the arms could have been associated with arterial hypertension. It is important, because major difference has been associated with poor outcome [5,6] and increased mortality [7], especially in individuals with arterial hypertension [8,9]. This correlation was also investigated by other authors.…”
Section: Discussionmentioning
confidence: 92%